THE EFFECT OF LEADERSHIP STYLE AND WOR DISCIPLINE ON EMPLOYEE PERFORMANCE WITH WORK MOTIVATION AS AN INTERVENING VARIABLE - Formaida Tambunan; Ruth Shofiyana Saragih; Rida Maswati Telambanua; Perdamaian Ndururu (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2025)
PURPOSE - Human resources are a factor that influences the performance and reputation of the company. Human resources in a company need to be managed professionally to create a balance between employee needs and the demands and capabilities of the company. This balance is the main key for the company to be able to develop productively and fairly. The purpose of this study is to determine whether there is an influence of leadership style and work discipline on employee performance with work motivation as an intervening variable.METHODOLOGY - This type of research is explanatory research. The population in this study were employees of PT. Perkebunan Nusantara IV Regional I Medan as many as 124 people and the research sample was the total population of 124 respondents. The data needed using a questionnaire with a Likert scale which was then analyzed using path analysis.FINDING - The results showed that : 1) Leadership style and work discipline affect employee performance. The better the leadership style of a leader, the better employee performance. Likewise, the higher the work discipline of an employee, the better the employee's performance. These two variables support each other in creating high employee performance, 2) Work motivation affects employee performance. The higher the employee's work motivation, the higher the employee's performance, 3) Work discipline has no effect on work motivation, 4) Work motivation has no effect on employee performance, 5) Leadership style and work discipline have no direct effect on employee performance through work motivation